Assessment of the efficiency of oxygen absorption in rotor-pulsating apparatus - Obodovych Oleksandr; Sydorenko Vitalii (Acta Periodica Technologica, 2018)
This work presents the results of a study of the oxygen absorption rate in water solutions in the setup consisting of a jet unit and disperser-mixer, which is a rotor-pulsating apparatus. The purpose of the work was to evaluate the efficiency of the rotor-pulsating apparatus in the aeration of aqueous solutions. The experimental data were obtained by the method of chemical oxidation of sodium sulfide, part of the model solution, with air oxygen,. The influence of the rotor rotational speed on the oxygen absorption rate was determined by experiments. A comparison of aeration conditions, sulfite number, and energy efficiency in relation to the corresponding characteristics of some pneumatic and mechanical aerators found in the literature is provided.